(untitled) (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2018)
INTRODUCTION: The objective of this research from the area of Speech Therapy specifically from the field of speech is to establish through a comprehensive review of the scientific evidence of which is the most effective test for the diagnosis of childhood stuttering. METHODS: Systematic review of descriptive type using search strategies in various databases in a 10-year timeline; that were studies in humans, child population, for the design of the question was used Pico methodology, to evaluate the quality of evidence was determined the use of the Grades system. RESULTS: this research yields the implementation of a standardized test for the assessment of the speaks to children with a stut-tering presence, this refers to Stuttering Instrumental Severity (SSI) with the evidence of reliability of GRADE. ANALYSIS AND DISCUSSION: the Instrumental Stuttering Severity examines the stutter-ing by means of the frequency, length of the phrase and time of the length of the sentence, emitting results for each subcomponent through the audio recordings made to the infants. CONCLUSIONS: the minimum bibliography on the different methods of speech evaluation is evidenced, therefore only instrumental stuttering was obtained, however, the GRADE methodology reliably demonstrates evi-dence from the sources entered.